The Literary Phenomenon in the Balance of Sociological Criticism – Patterns and Experiences - mebrak, hocine (El Omda in Linguistics and Discourse Analysis, 2022)
The sociological approach to literary criticism experienced a significant delay in comparison with other contextual critical methodologies. This delay is largely attributed to the reluctance of some researchers and scholars to accept a social interpretation of literature, based on the belief that the literary text should remain independent from scientific or social explanations. Moreover, they considered that the sociological approach was insufficient in explaining the literary phenomenon or in addressing it from an aesthetic or artistic perspective. However, this approach has managed to overcome many of the issues related both to methodology and to the literary product itself—namely the creator—and the outcome, namely the literary work. In doing so, it has made valuable contributions to criticism in general, helping to clarify the characteristics of the literary phenomenon.